Analysis of extemporal production trends in pharmacies for children - O. Zaliska; Y. Kacherai; Z. Zabolotnia; O. Semenov (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Medicines for children are insufficiently represented in pediatric dosages and appropriate dosage forms in the pharmaceutical market of Ukraine. Pediatricians are forced to prescribe children's medicines in dosages that are not available in the State Register of Medicines of Ukraine. Extemporaneously compounded medicines (ECM) are useful when a required dose or dose form is unavailable commercially, or is needed for individualised dosing. The aim of the study was to analysis a real data of the list of medicines which are produced in hospital and public pharmacies of Lviv region during 2020-2021. Methods. Content analysis of extemporal prescriptions for children, depending on the composition of the active pharmaceutical ingredient, dose and dosage form, comparative cost analysis of ECM and industrial medicines. In the hospital doctors prescribe ECМ in liquid forms (75%) - solutions for injection and in solid forms (25%) - dosed simple powders - 19%, dosed complex powders - 6%. It was determined the structure of ECM, which are produced in 6 studied pharmacies in 2020-2021. There are soft ECM 61.6% in dosage forms: ointments, creams, paste; liquid ECM are 28.3% in mixtures, solutions, mumbles; solid ECM are 8.3% in mono, combine powders, suppositories and 1.8% - other ECM: powders and nail polishs. There were highlighted unique recipes of ECM which analogues were not present in industrial dosage forms. We conducted analysis of the cost of children's ECM in these pharmacies. It was determined that ECM cost were 40.5-305.6 UAH depending on the dosage form. The comparative analysis showed that ECM are in 2.2-4.9 times more cheaper for children compare with similar active ingredients in industrial medicines. ECMs are much more compliant for treatment in children and babies, they provide higher effect, safety, reduce dosing errors, especially at the inpatient stage, and continuation of therapy on an outpatient basis and more cost-effective for individual needs. The use of ECMs allows parents to properly dose them for children, to avoid errors in dosing, improper administration, which is extremely important to ensure the rational use of medicines in pediatric practice.